In vivo analgesic, antipyretic and anti-inflammatory activities of ethanol extract of Pericampylus glaucus in experimental animals - Kifayatullah, Muhammad; Rahim, Haroon; Jan, Naeem Ullah; Ahmad Chishti, Kamran; Ullah, Irfan; Abbas, Sudair (Penerbit Universiti Kebangsaan Malaysia, 2019)
Pericampylus glaucus is a common Malaysian plant used traditionally in the treatments of joint pain, abdominal pain and headache. Hence, the present research was aimed to evaluate ethanolic extract of Pericampylus glaucus for analgesic, antipyretic and anti-inflammatory activities in experimental animals. The central and peripheral analgesic activity was determined by acetic acid induced writhing and hot plate method by examining the number of writhing and paw licking or jumping time. Meanwhile, the antipyretic activity was determined by Brewer’s yeast- test that induced pyrexia and carrageenan- that induced hind paw inflammation was used for anti-inflammatory activities. The ethanolic extract of Pericampylus glaucus at doses (300 and 600 mg/kg b.wt) and Ibuprofen (100 mg/kg (b.wt) was used as a reference drug in the whole experiment. Intraperitoneal administration of Pericampylus glaucus produced significant (p<0.01) inhibition in writhing response in acetic acid induced writhing test and dose-dependent (p<0.001) prolonged paw licking in hot plate test as compared to control (normal saline treated group). Similarly, significant (p<0.001) attenuation in lowering rectal temperature was noted in animal groups that were treated with ethanolic extract of Pericampylus glaucus at different doses. The attenuation was, almost the same as produced by ibuprofen treated group. Furthermore, Pericampylus glaucus extract also produced significant reduction in hind paw edema (p<0.001), 4 h after administration of carrageenan and inhibition was 60.19% and 42.17% as compared to control (normal saline treated group). The findings of this study indicated that Pericampylus glaucus possess significant analgesic, antipyretic and anti-inflammatory activities and could possibly be used in the management of fever, pain and inflammation.